KONSTRUKSI IDENTITAS MAHASISWA DALAM BERMEDIA SOSIAL: (Studi Kasus 4 Mahasiswa FIS UNJ Pengguna Media Sosial Instagram) - Balqis Aisyah, Annya; Eva Rosalia, Carissa; Danu Ayustina, Fitri; Iqbal Fawwaz, Muhammad (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2021)
This study aims to determine the construction of student identity in social media. This research will use a digital ethnographic method with a case study approach. The results of this study explain how the construction of student identity in social media Instagram, this is also related to active users of social media which are mostly used by teenagers. In the use of social media, Instagram itself has various motives and goals which are not only to show daily life but also to display self-image through cyberspace. The identity shown by students through Instagram in the discussion of this research is in line with Peter L. Berger's concept of the concept of identity construction which will be used as research analysis and is equipped with Erving Goffman's impression management concept.